KiDS-Legacy: Angular galaxy clustering from deep surveys with complex selection effects - Yan, Ziang; Wright, Angus H.; Chisari, Nora Elisa; Georgiou, Christos; Joudaki, Shahab; Loureiro, Arthur; Reischke, Robert; Asgari, Marika; Bilicki, Maciej; Dvornik, Andrej; Heymans, Catherine; Hildebrandt, Hendrik; et al. (EDP Sciences, 2025)
Photometric galaxy surveys, despite their limited resolution along the line of sight, encode rich information about the large-scale structure (LSS) of the Universe thanks to the high number density and extensive depth of the data. However, the complicated selection effects in wide and deep surveys can potentially cause significant bias in the angular two-point correlation function (2PCF) measured from those surveys. In this paper, we measure the 2PCF from the newly published KiDS-Legacy sample. Given an r-band 5σ magnitude limit of 24.8 and survey footprint of 1347 deg2, it achieves an excellent combination of sky coverage and depth for such a measurement. We find that complex selection effects, primarily induced by varying seeing, introduce over-estimation of the 2PCF by approximately an order of magnitude. To correct for such effects, we apply a machine learning-based method to recover an organised random (OR) that presents the same selection pattern as the galaxy sample. The basic idea is to find the selection-induced clustering of galaxies using a combination of self-organising maps (SOMs) and hierarchical clustering (HC). This unsupervised machine learning method is able to recover complicated selection effects without specifying their functional forms. We validate this SOM+HC method on mock deep galaxy samples with realistic systematics and selections derived from the KiDS-Legacy catalogue. Using mock data, we demonstrate that the OR delivers unbiased 2PCF cosmological parameter constraints, removing the 27σ offset in the galaxy bias parameter that is recovered when adopting uniform randoms. Blinded measurements on the real KiDS-Legacy data show that the corrected 2PCF is robust to the SOM+HC configuration near the optimal set-up suggested by the mock tests.
Keywords: cosmological parameters; cosmology: observations; large-scale structure of Universe; methods: data analysis; methods: statistical; Astronomy and Astrophysics; Space and Planetary Science